Mengembangkan Kecerdasan Intrapersonal Anak Melalui Bermain Puzzle di RA Annajamissa’adah - Fauziah Nasution; Fatimah Fatimah; Ika Holpiana Sari Marbun; Siti Khairiyah; Nur Rizkiya Makhfiro Nasution (Inovasi Pendidikan dan Anak Usia Dini, 2025)
prevalent Intrapersonal intelligence is a person's ability to understand himself. Intrapersonal intelligence can be developed through puzzle play. Puzzle is a game consisting of pieces of one 2 particular image. intrapersonal intelligence that is developed through playing puzzles, namely the ability to be responsible and the ability to obey the rules. The formulation of the problem in this study is whether children's intrapersonal intelligence can develop through puzzle-playing activities at the RA Annajamissa’adah. The purpose of this study was to determine the development of intrapersonal intelligence of children through playing puzzles in the RA Annajamissa’adah. The research approach used is a qualitative approach using the experimental method. The subjects of this study were 5 children aged 4-5 years, all of whom were male. Data collection techniques used were the initial observation (pretest) and final observation (posttest). The initial observation is carried out before the treatment is given using a media puzzle and the final observation is carried out after the treatment is given. The results of the study showed that 4 out of 5 people were capable of being responsible, and the ability to obey the rules reached a value of 3 out of 4 values, namely with the statement of DAE (Developing According to Expectations). Thus the intrapersonal intelligence of children. aged 4-5 years in the RA Annajamissa’adah Regency can develop through puzzle play.